8,4'-Oxyneolignane glucosides from an aqueous extract of "ban lan gen" (Isatis indigotica root) and their absolute configurations - Lingjie Meng; Qinglan Guo; Yufeng Liu; Jiangong Shi (Elsevier, 2017)
Three pairs of glycosidic 8,4'-oxyneolignane diastereoisomers, named isatioxyneolignosides A−F (1-6), were isolated from an aqueous extract of Isatis indigotica roots. Their structures and absolute configurations were elucidated by comprehensive spectroscopic data analysis and enzyme hydrolysis. The validity of ΔδC8-C7 values to distinguish threo and erythro aryl glycerol units and Cotton effects at 235±5 nm to determine absolute configurations at C-8 in 1-6 and their aglycones (1a-6a) are discussed.